Amphibian diversity in the Amazonian floating meadows: a Hanski core‐satellite species system. Issue 9 (9th June 2021) - Fonte, Luis Fernando Marin da; Latombe, Guillaume; Gordo, Marcelo; Menin, Marcelo; de Almeida, Alexandre Pinheiro; Hui, Cang; Lötters, Stefan
Abstract : The Amazon catchment is the largest river basin on earth, and up to 30% of its waters flow across floodplains. In its open waters, floating plants known as floating meadows abound. They can act as vectors of dispersal for their associated fauna and, therefore, can be important for the spatial structure of communities. Here, we focus on amphibian diversity in the Amazonian floating meadows over large spatial scales. We recorded 50 amphibian species over 57 sites, covering around 7000 km along river courses. Using multi‐site generalised dissimilarity modelling of zeta diversity, we tested Hanski's core‐satellite hypothesis and identified the existence of two functional groups of species operating under different ecological processes in the floating meadows. 'Core' species are associated with floating meadows, while 'satellite' species are associated with adjacent environments, being only occasional or accidental occupants of the floating vegetation. At large scales, amphibian diversity in floating meadows is mostly determined by stochastic (i.e. random/neutral) processes, whereas at regional scales, climate and deterministic (i.e. niche‐based) processes are central drivers. Compared with the turnover of 'core' species, the turnover of 'satellite' species increases much faster with distances and is also controlled by a wider range of climatic features. Distance is not a limiting factor for 'core' species, suggesting that they have a stronger dispersal ability even over large distances. This is probably related to the existence of passive long‐distance dispersal of individuals along rivers via vegetation rafts. In this sense, Amazonian rivers can facilitate dispersal, and this effect should be stronger for species associated with riverine habitats such as floating meadows.